Macropharyngodon pakoko, a new species of wrasse (Teleostei: Labridae) endemic to the Marquesas Islands, French Polynesia - Delrieu-Trottin, Erwan; Williams, Jeffrey T.; Planes, Serge (Zootaxa, 2014)
A new species of wrasse, Macropharyngodon pakoko, is described from the Marquesas Islands, bringing the total number of species of the genus Macropharyngodon to 12. Macropharyngodon pakoko was found at depths from 0-42 m and is endemic to the Marquesas Islands. Macropharyngodon pakoko is similar to M. meleagris, which is widely distributed from the central and western Pacific to Cocos-Keeling in the Indian Ocean, but differs genetically and in several coloration characters: males with irregularly curved black humeral blotch with incomplete iridescent blue border; inverted irregular “U”- shaped band on the cheek; a small black spot at the upper base of the pectoral fin; and background color of the body greenish with faint bluish black spots on each scale. Females lack black pigment on the chest posterior to the ventral attachment of the gill membranes; reddish black blotches on the body are widely spaced, particularly on the head where they are more reddish and half the size of those on body; caudal fin with small, bright yellow spots arranged in narrow vertical bands with pale interspaces; pelvic fins pale with three reddish yellow cross-bands; a small black spot at the upper base of the pectoral fin; and small reddish spots along the base of the anal fin. Juveniles have irregular black blotches on the body, a small black spot instead of an ocellus posteriorly on the dorsal fin and lack large black spots and ocellus on the anal fin.